2016
DOI: 10.1080/02699931.2016.1145105
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance for approach of ambiguity in social anxiety disorder

Abstract: Previous research has utilized the approach avoidance task (AAT) to measure approach and avoidance action tendencies in socially anxious individuals. “Neutral” social stimuli may be perceived as ambiguous and hence threatening to socially anxious individuals, however it is unclear whether this results in difficulty approaching ambiguous (“neutral”) versus unambiguous threat (e.g., disgust) faces (i.e., intolerance of ambiguity). Thirty participants with Social Anxiety Disorder (SADs) and 29 non-anxious control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Finally, many studies may not always accurately identify biases in relation to threat due to differences in threat evaluations. For instance, all facial stimuli may be considered somewhat threatening in socially anxious individuals, and as such avoidance of all faces may occur 59 . Avoidance of all perceived social threat may mask any group differences in attention bias picked up with current measures, as only between-face differences are generally calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, many studies may not always accurately identify biases in relation to threat due to differences in threat evaluations. For instance, all facial stimuli may be considered somewhat threatening in socially anxious individuals, and as such avoidance of all faces may occur 59 . Avoidance of all perceived social threat may mask any group differences in attention bias picked up with current measures, as only between-face differences are generally calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are indications that J o u r n a l P r e -p r o o f individuals with SAD are characterized by intolerance of uncertainty (Boelen & Reijntjes, 2009;Lange, Allart, Keijsers, Rinck, & Becker, 2012). For instance, Kuckertz, Strege, and Amir (2017) found that participants with SAD showed less willingness to approach neutral faces relative to disgusting faces, which is compatible with neutral facial expressions inducing social uncertainty regarding another person's feelings or intentions.…”
Section: Social Anxietymentioning
confidence: 97%
“…Bayani reported that students with higher levels of social phobia have poor problemsolving ability and greater depression (20). It has also been shown that social phobia is correlated with adjustment problems (21), intolerance of ambiguities (22), mood disorders (23), increase in cigarette and marijuana use (24), social isolation (25), QOL (26), avoidant personality (27,28), and bipolar disorder (29). Personality and psychopathology are two categories of the field of psychology, which have gained the interest of many researchers.…”
Section: Introductionmentioning
confidence: 99%